RESTRICTION OF FREEDOM OF EXPRESSION OF POLITICAL VIEWS IN MARTIAL LAW - BAITALYUK, ZORYANA (Ehrlich's Journal, 2023)
The article examines the issue of restrictions on freedom of expression under martial law. Freedom of political expression is defined as the right of every person to freely express his or her political views and assess historical events of a political nature and current political processes and phenomena in a manner prescribed by law. Support for freedom of expression is characterized as one of the important guarantees for the development and protection of democracy. Thanks to the right to freedom of political expression, modern democratic states find the most optimal solutions to the socio-political and legal challenges that arise in the course of their functioning. It is noted that due to the ability to freely express oneself, criticize the authorities, hold certain political views and freely promote them, everyone has the opportunity to influence the democratic institutions of their state and be an active participant in political processes in it. The author emphasizes that freedom of expression should be classified as the so-called “immutable core of human rights” along with the right to life, prohibition of torture and inhuman or degrading treatment, the right to a fair trial, and the right not to be subjected to enforced disappearance. It is noted that restrictions on freedom of expression are the basis for the existence of democratic institutions and the rule of law, civil society and the realization of most human rights. At the same time, such restrictions should be imposed as an exception and solely for the purpose of protecting the rights of an individual. The purpose of such restrictions should be proportionate to the means of achieving it. It is emphasized that the criteria for limiting the right to freedom of expression should be established exclusively in law. In turn, the law should be accessible, specific and sufficiently clear.